2014
DOI: 10.1002/jppr.1029
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot versus continuous documentation of pharmacists’ interventions: are snapshots worthwhile?

Abstract: Background:The documentation of pharmacists' interventions is important but there are limited studies evaluating the different methods of documentation.Aim: To compare the nature of pharmacists' interventions documented during snapshots versus direct observation in a paediatric hospital and to gather pharmacists' opinions on the utility of the different documentation methods. Method:The pattern and rates of pharmacists' interventions from the snapshot reports and direct observation were compared across five st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…the ward type, time allocation and pharmacist's experience . Furthermore, as discussed earlier, pharmacist interventions are often under‐documented …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the ward type, time allocation and pharmacist's experience . Furthermore, as discussed earlier, pharmacist interventions are often under‐documented …”
Section: Discussionmentioning
confidence: 99%
“…Selected studies conducted in Australia and overseas have focused on analysing pharmacists’ intervention records and reported that pharmacists prevented MRPs, including potentially serious prescribing errors . Although these studies highlighted the clinical significance of medication errors and the important role of hospital pharmacists in identifying and preventing medication errors, many of the reports evaluated short‐term data collected over periods of <12 months .…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacist interventions are often reported to be under-documented. 11 Furthermore, the number of surveys received from patients is relatively small and does not represent all at PAC. During the evaluation, several PAC appointments were moved to telephone consults due to the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of whether this was due to pharmacists’ time restrictions or whether it is influenced by the nature of the interventions and their clinical significance, relying on evaluating the impact of clinical interventions using the data from iPharmacy ™ alone vastly underestimates the contribution that pharmacists make to optimising patient care. Alternative, less labour intensive ways of collecting and collating data relating to pharmacists’ interventions has been described elsewhere but requires future exploration …”
Section: Discussionmentioning
confidence: 99%